2014
DOI: 10.1016/j.ejphar.2013.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular calcium channels in protozoa

Abstract: Ca2+-signaling pathways and intracellular Ca2+ channels are present in protozoa. Ancient origin of inositol 1,4,5-trisphosphate receptors (IP3Rs) and other intracellular channels predates the divergence of animals and fungi as evidenced by their presence in the choanoflagellate Monosiga brevicollis, the closest known relative to metazoans. The first protozoan IP3R cloned, from the ciliate Paramecium, displays strong sequence similarity to the rat type 3 IP3R. This ciliate has a large number of IP3- and ryanodi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 176 publications
(306 reference statements)
0
30
0
Order By: Relevance
“…Specific searches in the T. gondii genome, as well as in other Apicomplexan genomes, have revealed no evidence for the existence of STIM or ORAI (27,28), in agreement with our results on the absence of SOCE in T. gondii. It is interesting to note, however, that evidence for the presence of STIM and ORAI orthologs has been reported in other unicellular protists, like the choanoflagellate Monosiga brevicollis, which belongs to the supergroup Ophisotkonta, which also includes animals and fungi (11,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specific searches in the T. gondii genome, as well as in other Apicomplexan genomes, have revealed no evidence for the existence of STIM or ORAI (27,28), in agreement with our results on the absence of SOCE in T. gondii. It is interesting to note, however, that evidence for the presence of STIM and ORAI orthologs has been reported in other unicellular protists, like the choanoflagellate Monosiga brevicollis, which belongs to the supergroup Ophisotkonta, which also includes animals and fungi (11,29).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that intracellular Ca 2ϩ stores are important for initiation of gliding motility (5), microneme secretion (6), conoid extrusion (7), active parasite invasion (8 -10), and egress (8) (reviewed in Ref. 11), but the role of extracellular Ca 2ϩ in these processes was not studied in detail or was considered minor.…”
Section: Elevation In Cytoplasmic Camentioning
confidence: 99%
“…In T. brucei the IP 3 R localizes to acidocalcisomes rather than to the ER [4,5]. The acidocalcisome localization was first reported using the epitope-tagged protein [4,5] and recently confirmed using specific antibodies against TbIP 3 R [67].…”
Section: Transport Mechanisms Of Intracellular Organellesmentioning
confidence: 99%
“…The acidocalcisome localization was first reported using the epitope-tagged protein [4,5] and recently confirmed using specific antibodies against TbIP 3 R [67]. As indicated above (Section 4.1) evidence for ER localization in T. cruzi [54] is weak and contradicts proteomic analyses of acidocalcisomes and contractile vacuole complex of these parasites that provided evidence for the presence of the TcIP 3 R ortholog in these organelles [33].…”
Section: Transport Mechanisms Of Intracellular Organellesmentioning
confidence: 99%
See 1 more Smart Citation